Upaya Hukum dalam Pencegahan Klaim Tiongkok terhadap Laut Natuna Utara - Budiono, Indro; Anggriawan, Ferry; Kusumandaru, Pena (University of Merdeka Malang, 2024)
The United Nations Convention on the Law of the Sea (UNCLOS) in 1982 is an international legal The United Nations Convention on the Law of the Sea (UNCLOS) in 1982 is an international legal instrument that plays a key role in regulating the rights and obligations of countries related to the global use of the sea. Territorial conflicts in the North Natuna Sea, especially China's claims that are not by UNCLOS, are a serious challenge for Indonesia in upholding its maritime sovereignty. The 2016 South China Sea Arbitration Award, which rejected China's